Towards an Information Infrastructure for Medical Image Sharing. - Motta, Gustavo H. M. B.; Araújo, Danilo A. B.; Lucena-Neto, Juracy R.; Azevedo-Marques, Paulo M.; Cordeiro, Saulo S.; Araújo-Neto, Severino A. (Journal of Digital Imaging, 2020)
Information infrastructures involve the notion of a shared, open infrastructure, constituting a space where people, organizations, and technical components associate to develop an activity. The current infrastructure for medical image sharing, based on PACS/DICOM technologies, does not constitute an information infrastructure since it is limited in its ability to share in a scalable, comprehensive, and secure manner. This paper proposes the DICOMFlow, a decentralized, distributed infrastructure model that aims to foment the formation of an information infrastructure in order to share medical images and teleradiology. As an installed base, it uses the PACS/DICOM infrastructure of radiology departments and the internet e-mail infrastructure. Experiments performed in real and simulated environments have indicated the feasibility of the proposed infrastructure to foment the formation of an information infrastructure for medical image sharing and teleradiology.